Compensation management in Poland - Thomas Otte (Journal for East European Management Studies, 2003)
The paper looks at different aspects of compensation management in Polandbased corporations. It identifies geography, ownership and industry as the most important factors for wage differentiation within the Polish labor market. Another essential finding is that the companies primarily use specific Polish methods of job evaluation for determining the base salary of their employees and that there are still certain methodological problems in this area of compensation management. Polish corporations also take a more and more systematic approach in the area of performance appraisal and variable pay as well as in the field of incentives management. Finally, the issue of social insurance contributions is covered. – – Der Beitrag befasst sich mit verschiedenen Aspekten der Entgeltgestaltung in polnischen Unternehmen. Geographischer Standort, Eigentumsform und Branchenzugehörigkeit werden als die wichtigsten Faktoren der Entgeltdifferenzierung identifiziert. Weiterhin wird deutlich, dass die Unternehmen zur Bestimmung des Basisgehalts in erster Linie spezifische polnische Methoden der Arbeitsbewertung verwenden und dass es dabei teilweise noch erhebliche methodische Probleme gibt. Polnische Unternehmen gehen in Bereichen wie Leistungsbewertung, variabler Entgeltgestaltung und Incentives Management zunehmend systematisch vor. Abschließend geht der Beitrag auf das Thema Sozialabgaben ein.
Keywords: 650; compensation management; job evaluation; performance appraisal; IT market; IT sektor